(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article presents a comparative analysis of the synonym system in the French and Uzbek languages. The synonym series of the two languages, their structure, semantic features, ways of formation and areas of application are studied. The analytical structure of the French language and the agglutinative features of the Uzbek language are analyzed to determine how they affect the formation of synonyms. Using the comparative-typological method, the universal and specific aspects of synonymous relations in the two languages are identified.